1991
DOI: 10.1111/j.1600-0897.1991.tb00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression by Human Placental Protein 14 of Natural Killer Cell Activity

Abstract: Human decidua of early pregnancy contains considerable numbers of CD3-CD56+ natural killer (NK) cells. In this study, two major protein products of the decidua, placental protein 14 (PP14) and placental protein 12 (PP12), were tested for the ability to regulate human NK cell activity. In vitro overnight exposure to PP14 of blood lymphocytes or purified large granular lymphocytes (LGL) resulted in suppression of cytotoxicity against K562 target cells in a 4-h 51Cr release assay. The NK inhibition was dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
94
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 212 publications
(99 citation statements)
references
References 21 publications
(4 reference statements)
1
94
0
2
Order By: Relevance
“…Our results indicate that Gp can induce VEGF expression in some cell lines and VEGF receptor Flt-1 in HUVECs. Glycodelin usually has been considered to play an immunosuppressive function in embryo implantation and tumor development (18,19). Our results suggest that glycodelin also might play an important role in embryogenesis and tumor development by inducing angiogenesis.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Our results indicate that Gp can induce VEGF expression in some cell lines and VEGF receptor Flt-1 in HUVECs. Glycodelin usually has been considered to play an immunosuppressive function in embryo implantation and tumor development (18,19). Our results suggest that glycodelin also might play an important role in embryogenesis and tumor development by inducing angiogenesis.…”
Section: Discussionmentioning
confidence: 55%
“…A potential role for glycodelin in embryonic implantation has been confirmed as facilitating evasion of the maternal immune response (17)(18)(19). The biological function of glycodelin in tumor has not been clarified yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Morrow et al have shown that PP14 is expressed by haematopoietic cells of the megakaryocytic lineage and demonstrates potent immunosuppressive properties which can be blocked by PP14-specific antibodies [92]. PP14 has also been reported to suppress the activity of natural killer cells and T-cells [93]. Seppala et al recently reviewed other immunoregulatory properties of PP14 [94].…”
Section: Immune Modulationmentioning
confidence: 99%
“…Apart from this, PP14 has been shown to have immunosuppressive properties in that it inhibits both phytohemagglutinin (14) and anti-CD3 antibody-induced lymphocyte proliferation (15). PP14 also inhibits Natural Killer cell activity (16). That the protein is essential for normal pregnancy progression has been established by the association of low levels of PP14 with habitual abortion (17,18), unexplained infertility (19), and establishment of pregnancy in women during those cycles in which normal concentrations of PP14 were detected (20).…”
mentioning
confidence: 99%